Targeting Sphingosine Kinase Isoforms Effectively Reduces Growth and Survival of Neoplastic Mast Cells With D816V-KIT - Bandara, Geethani; Muñoz-Cano, Rosa; Tobío, Araceli; Yin, Yuzhi; Komarow, Hirsh D.; Desai, Avanti; Metcalfe, Dean D.; Olivera, Ana (Frontiers in Immunology, 2018)
Mastocytosis is a disorder resulting from an abnormal mast cell (MC) accumulation in tissues that is often associated with the D816V mutation in KIT, the tyrosine kinase receptor for stem cell factor. Therapies available to treat aggressive presentations of mastocytosis are limited, thus exploration of novel pharmacological targets that reduce MC burden is desirable. Since increased generation of the lipid mediator sphingosine-1-phosphate (S1P) by sphingosine kinase (SPHK) has been linked to oncogenesis, we studied the involvement of the two SPHK isoforms (SPHK1 and SPHK2) in the regulation of neoplastic human MC growth. While SPHK2 inhibition prevented entry into the cell cycle in normal and neoplastic human MCs with minimal effect on cell survival, SPHK1 inhibition caused cell cycle arrest in G2/M and apoptosis, particularly in D816V-KIT MCs. This was mediated via activation of the DNA damage response cascade, including phosphorylation of the checkpoint kinase 2 (CHK2), CHK2-mediated CDC25c depletion and p53 activation. Combination treatment of SPHK inhibitors with KIT inhibitors showed greater growth inhibition of D816V-KIT MCs than either inhibitor alone. Furthermore, inhibition of SPHK reduced the number of malignant bone marrow MCs from patients with mastocytosis and the growth of D816V-KIT MCs in a xenograft mouse model. Our results reveal a role for SPHK isoforms in the regulation of growth and survival in normal and neoplastic MCs and suggest a regulatory function for SPHK1 in the DNA damage response in MCs with KIT mutations. The findings also suggest that targeting the SPHK/S1P axis may provide an alternative to tyrosine kinase inhibitors, alone or in combination, for treatment of aggressive mastocytosis and other hematological malignancies associated with the D816V-KIT mutation.